Motivation Analysis on Employee Performance in Agencies Medan Helvetia Sub-district Office Government Job Satisfaction Mediated - Muhammad Ludfi; Sri Rahayu; Muhammad Chaerul Rizky (International Journal of Management, Economic and Accounting, 2024)
Trust in ensuring government and commercial institutions is necessary for long-term effectiveness. This trust is an important aspect in society. Alternatively, some companies may experience a crisis in which they fall victim to public trust, giving rise to distrust of the organization. The aim of this research is to analyze and determine the influence motivation on the job satisfaction of the Medan Helvetia Distric Head Office, and to analyze the influence of employee performance which is mediated by job satisfaction in Medan Helvetia Distric Head Office. The sample type for this research is descriptive quantitative, the research consisted of 50 people, the data was analyzed using the SEM (structural equation modeling) method. Overall, from the results and discussion in the research, it is concluded that there is a positive and significant influence between motivation variables are able to job satisfaction on employee performance in the Medan Helvetia Distric Head Office